Successful Treatment of Candida parapsilosis Fungemia in Two Preterms with Voriconazole - Emel Altuncu; Hulya Bilgen; Ahmet Soysal; Eren Ozek (Case Reports in Pediatrics)
Herein, we report two preterms with invasive candidiasis refractory to liposomal amphotericin B (AMB) treatment in spite of low MIC levels (MIC: 0.5 mcg/mL). Both of the patients’ blood cultures were persistently positive for C. parapsilosis despite high therapeutic doses (AMB: 7 mg/kg per day). After starting voriconazole blood cultures became negative and both of the patients were treated successfully without any side effects. In conclusion, although it is not a standard treatment in neonatal patients, our limited experience with these patients suggests that voriconazole appears to be a safe antifungal agent to be used in critically ill preterm infants with persistent fungemia despite AMB treatment.